PERCUTANEUS NEPHROSTOMY IN PATIENTS WITH OBSTRUCTIVE UROPATHY DUE TO MALIGNANCY: A SURVIVAL ANALYSIS - Yuri, Prahara; Rochadi, Sungsang (Indonesian Journal of Urology, 2016)
Objective:To find out effectiveness of percutaneous nephrostomy (PCN) and patient survival rate as palliative decompression of the obstructed urinary system due to malignancy (urogenital neoplasias). Materials & Methods: A cohort retrospective study was performed with 76 patients (58 female and 18 male) with malignancy process who were undergoing percutaneous nephrostomy during January 2009 – December 2012, in Sardjito General Hospital Yogyakarta. Survival analysis was done by Kaplan-Meier method and differences were assessed using the log-rank test. Results:There was no procedure-related mortality. The mean of age was 49.14 years. The primary tumoral site was the uterine cervix in 56.6 %, the bladder in 17.1 %, the prostate in 2.6% and other sites (intestinal, ovarium and other malignancies caused obstructive uropathy) in 23.7%. The patients died during the hospitalization period due to advanced neoplasia are 17.1%. The mortality rate was higher in patients with interval between diagnose of obstructive uropathy and nephrostomy > 7 days (HR=5.7; 95%CI 4.5-6.9; p = 0.001) and in those who required hemodialysis before the procedure (HR=6.1; 95%CI 4.7-7.4; p = 0.001). The survival rate was 55.2% (42/76) at 6 months and 32.9% (25/76) at 12 months. The percentage of the lifetime spent in hospitalization was 17.1% (13/76). There are no differences on survival rate in that patients based on neoplasias type and age.Conclusion: The urinary obstruction must be immediately relieved. The percutaneous nephrostomy is a safe and effective method for relief the obstruction. Patient with hemodialysis before the procedure had a poor prognosis.